A Randomized Trial of Epidural Analgesia Followed by Continuous Femoral Analgesia Compared with Oral Opioid Analgesia on Short- and Long-Term Functional Recovery After Total Knee Replacement - Nader, Antoun; Kendall, Mark C.; Wixson, Richard L.; Chung, Brian; Polakow, Linda M.; McCarthy, Robert J. (Pain medicine (Malden, Mass.), 2012)
Objective.  The purpose of this study was to compare continuous femoral nerve analgesia to oral opioid analgesics after discontinuation of epidural analgesia following total knee replacement. Design.  Randomized prospective controlled parallel group trial. Setting.  Large tertiary university teaching hospital in a major Midwestern city. Subjects.  Sixty‐two subjects were randomized to receive neuraxial anesthesia followed by either oral analgesics (N = 31) or continuous femoral nerve analgesia (N = 31). Interventions.  After discontinuation of epidural anesthesia on the morning after surgery, continuous femoral nerve analgesia (CFA), ropivacaine 25 mg bolus and 5 mg/h infusion was initiated. Catheters were removed 24 hours later. All subjects received oral opioid analgesics as needed. Outcome Measures.  The primary outcome measure was knee flexion at 1 month. Physical therapy assessments, pain scores, opioid consumption, and patient satisfaction were assessed during hospitalization. Knee flexion, pain scores, and opioid consumption were collected at 1, 6, and 12 months, and health‐related quality of life was collected at 6 and 12 months. Results.  The median difference (95% CI) in the change in knee flexion from baseline was 7.5 (0 to15) degrees greater after CFA (P = 0.04) at 1 month. CFA subjects had greater compliance with physical therapy, reduced pain scores, and opioid requirements during hospitalization. Thromboembolic events occurred in 0/31 CFA vs 4/31 non‐CFA subjects (P = 0.04). Conclusions.  CFA for 24 hours following discontinuation of epidural analgesia was associated with lower pain scores, greater compliance with physical therapy, increased range of motion, reduced opioid analgesia use, and greater patient satisfaction during hospitalization. The increased flexion of the operated joint was still evident at 1 month postoperatively.